Institute of consent with accusation in criminal proceedings of Russia and foreign countries - Shumilin, Sergey F.; Kolmakov, Petr A.; Nasonov, Aleksander A.; Novikova, Ekaterina A.; Shumilina, Oksana S. (Linguistics and Culture Review, 2021)
The current study attempts to present the effects of a comparative legal study regarding the legal consequences of consent with accusation in Russia and foreign countries' criminal processes. It has been established that the institution of consent with accusation in the Russian criminal process does not have a significant effect on its reduction and also does not determine the development and application of alternative measures of punishment for committing crimes. According to the current Criminal Procedure Code of Russia, consent with accusation concerning committing crimes of small and medium gravity entails the same consequences: release from criminal liability and reduction of the amount of punishment. Following the principle of fairness, the authors substantiated the most appropriate alternative penalties provided by the criminal procedure legislation of Germany and France.